Characteristics On Culinary Packaging Design Of Ayam Betutu In Denpasar - Ni Luh Desi In Diana Sari; Ni Ketut Pande Sarjani (Institut Seni Indonesia Denpasar, 2016)
The specific objective to be achieved in this research is to identify the characteristics of packaging design that is used to package a culinary ayam betutu in the city of Denpasar. Results of identification by the helpful to formulate criteria for packaging culinary design of/lyum Betutu, which can be used as a guide in creating innovative packaging design (Packaging Design Brief).This research is a qualitative descriptive study. Sources of data obtained through purposive sampling method performed by accidental sampling technique. Sampling is performed in the restaurant as a place selling Ayam Betutu which are spread throughout the city of Denpasar. Data collection techniques performed through observation, documentation and interview.The results achieved are the types of packaging used to pack a culinary of Ayam Betutu in the city of Denpasar. Collecting the results are determined based on the classiï¬cation of materials, visual appeal, the appeal of practical and packaging criteria.Keywords: Packaging design, Ayam Betutu, Denpasar, Bali typical souvenirs.